2022
DOI: 10.1208/s12249-022-02463-x
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices and Guidelines (2022) for Scale-Up and Tech Transfer in Freeze-Drying Based on Case Studies. Part 1: Challenges during Scale Up and Transfer

Abstract: The freeze-drying process scale-up and transfer remain a complicated and non-uniform practice. We summarized inefficient and good practices in these papers and provided some practical advice. It was demonstrated that using the same process set points/times in laboratory and commercial scale dryers may lead to loss of product quality (collapse or vial breakage). The emerging modeling approach demonstrated practical advantages. However, the upfront generation of some input parameters (vial heat transfer coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been suggested, for example, that the crystallization of a bulking agent during cooling can be beneficial in minimizing vial breakage. A case study that describes vial breakage as the result of annealing, and prevention of the vial breakage using step-wise cooling, is provided [32]. Also, the impact of timing of crystallization of the bulking agent (e.g., if it takes place during cooling or at the beginning of primary drying) during freeze-drying on protein stability was reported in [33]; in that case, crystallization of solute during cooling was beneficial for stability.…”
Section: Partially Crystalline Formulationsmentioning
confidence: 99%
“…It has been suggested, for example, that the crystallization of a bulking agent during cooling can be beneficial in minimizing vial breakage. A case study that describes vial breakage as the result of annealing, and prevention of the vial breakage using step-wise cooling, is provided [32]. Also, the impact of timing of crystallization of the bulking agent (e.g., if it takes place during cooling or at the beginning of primary drying) during freeze-drying on protein stability was reported in [33]; in that case, crystallization of solute during cooling was beneficial for stability.…”
Section: Partially Crystalline Formulationsmentioning
confidence: 99%
“…While many tools and approaches were developed to assist in lyophilization cycle optimization at laboratory scale [1], establishing commercial processes at any scale is a complicated process due to numerous challenges that could arise with the change in scale. The challenges during lyophilization process scale-up and transfer were outlined and discussed in the first part of this paper [2]. It was demonstrated that due to differences in refrigeration capacity, shelf mass, and heat transfer coefficients between commercial and laboratory dryers, the same process parameters in laboratory scale may not be applied to commercial dryers.…”
Section: Introductionmentioning
confidence: 99%
“…Various examples of mechanistic models of the primary drying phase describing this complex interplay of parameters have been developed ( Tang and Pikal, 2004 ; Fissore and Pisano, 2015 ; Mortier et al, 2016 ). For an in-depth recommendation on freeze-drying model practices the reader is referred to the literature ( Nail et al, 2017 ; Tchessalov et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%